Assessment of glycemic control and duration of diabetes in distal symmetric diabetic polyneuropathy - Kılıçaslan, Ferhat; Örtlek, Nurnihan; Geyik, Sırma (Acta Medica, 2025)
Diabetes is widespread disease that lead many complications. One of most common complication is neuropathy. However precise pathophysiological mechanism is still not understanding clearly. With this study we hope that we can understand either duration or severity of diabetes causes more trouble.